2010
DOI: 10.4174/jkss.2010.78.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs Transumbilical Single-Port Laparoscopic Appendectomy; Results of Prospective Randomized Trial

Abstract: Purpose: Conventional three-port laparoscopic appendectomy (LA) is more commonly performed than transumbilical single port laparoscopic appendectomy (TUSPLA). In this report, we performed a prospective randomized study comparing the outcomes of LA and TUSPLA. Methods: Between April 14, 2009 and June 10, 2009, 40 patients who required laparoscopic appendectomies were randomly selected to receive either a TUSPLA or a LA. None of these patients had perforation or abscess. Twenty of the patients received a LA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 20 publications
4
67
1
1
Order By: Relevance
“…Mean number of intravenous doses required was 1.4 in the SILS group and 1.2 in the CLA group and this difference in the analgesic requirement of the two groups was not statistically significant (p>0.05). Data published by Park JH et al 20 was in concordance with our study. In this study SILS group required 1.6 mean IV doses while CLA required 1.4 IV doses.…”
Section: Figure 2: Hr Usg Documenting Acute Appendicitissupporting
confidence: 83%
“…Mean number of intravenous doses required was 1.4 in the SILS group and 1.2 in the CLA group and this difference in the analgesic requirement of the two groups was not statistically significant (p>0.05). Data published by Park JH et al 20 was in concordance with our study. In this study SILS group required 1.6 mean IV doses while CLA required 1.4 IV doses.…”
Section: Figure 2: Hr Usg Documenting Acute Appendicitissupporting
confidence: 83%
“…The highest rates, however, were reported in papers using the 'SPILA unassisted' technique (2/10, 20%). 13 There were six intra-abdominal abscesses across all of the studies: five were reported in four 'SPILA unassisted' papers 9,11,19,21 and one in a 'hybrid' paper. 29 In total, complication rates appear to be highest for those procedures in which SPILA is not assisted by sutures or wire.…”
Section: Complication Ratesmentioning
confidence: 99%
“…Rothenburg et al placed a 3mm single instrument through a separate stab wound incision or 3mm port suprapubically to aid the SPILA procedure. 12 Palanivelu et al achieved successful SPILA The 'surgical glove' method (in which trocars are placed through the holes of a surgical glove with cut fingertips and the 'device' is subsequently applied to a retractor inserted into the abdomen through a single transumbilical incision) was described by Park et al, 19 Kim et al 20 and Lee et al 21 in 20, 43 and 75 patients respectively (Fig 2). The surgical glove can be considered an improvised multi-luminal single port device.…”
Section: Spila Unassistedmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve Potentially appropriate RCTs comparing SILA and CMLA were identified [10,11,12,13,14,15,16,17,18,19,20,21]. Among them, one study that applied a laparoscopic-assisted extracorporeal appendectomy technique was excluded [10].…”
Section: Resultsmentioning
confidence: 99%